Peran Arsiparis dalam Penerapan Arsip Dinamis di Biro Hubungan Masyarakat dan Umum LKPP - Abid Naufal Wiratama; Christian Wiradendi Wolor; Bayu Suhendry (INDO PUBLISHING, 2026)
This study aims to analyze the role of archivists in the implementation of dynamic archives management at the Public Relations and General Affairs Bureau of the National Public Procurement Agency (LKPP). The focus of this research includes the role of archivists in managing dynamic archives, the obstacles faced in its implementation, and the strategies used to improve the effectiveness of archives management. This study employed a qualitative approach using a descriptive method. Data collection techniques included observation, interviews, documentation, and the distribution of pre-research questionnaires. The research informants consisted of archivists and employees involved in archival management activities within the Public Relations and General Affairs Bureau of LKPP. Data analysis techniques were conducted through data reduction, data presentation, and conclusion drawing. The results of the study indicate that archivists play an important role in the implementation of dynamic archives management, starting from the processes of creation, classification, storage, maintenance, to retrieval of archives. Archivists also contribute to supporting archive digitization and maintaining institutional administrative order. However, the implementation of dynamic archives management at the Public Relations and General Affairs Bureau of LKPP has not been fully optimal due to several obstacles, such as limited facilities and infrastructure, the lack of fully integrated digital systems, inconsistent procedures across work units, and limited human resources with knowledge of digital archival systems. To overcome these challenges, archivists have implemented several strategies, including archival socialization, strengthening coordination among work units, reinforcing archive management procedures, and optimizing the use of technology in archival systems. This study concludes that the successful implementation of dynamic archives management is highly influenced by the competence of archivists, organizational policy support, and the availability of adequate facilities. Therefore, it is necessary to enhance human resource capacity, strengthen integrated digital systems, and provide continuous institutional support to ensure that dynamic archives management can be carried out more effectively, efficiently, and accountably.